Pentamidine Alleviates Inflammation and Lipopolysaccharide-Induced Sepsis by Inhibiting TLR4 Activation via Targeting MD2 - Wu, Siru; Lin, Cong; Zhang, Tianshu; Zhang, Bo; Jin, Yushan; Wang, Hongshuang; Li, Hongyuan; Wang, Yibo; Wang, Xiaohui (Frontiers in Pharmacology, 2022)
Toll-like receptor 4 (TLR4) is a pattern-recognition receptor (PRR), which can recognize lipopolysaccharides (LPS) and initiate the immune response, to protect the body from infection. However, excessive activation of TLR4 induced by LPS leads to the substantial release of pro-inflammatory factors, which may bring a cytokine storm in the body and cause severe sepsis. Existing molecules specialized in sepsis therapy are either in clinical trials or have mediocre effects. In this study, pentamidine, an approved drug used in the treatment of trypanosomiasis, was identified as a TLR4 antagonist. Saturation transferred difference (STD)-NMR spectra indicated that pentamidine directly interacted with TLR4′s co-receptor myeloid differentiation protein 2 (MD2) in vitro. Cellular thermal shift assay (CETSA) showed that pentamidine binding decreased MD2 stability, which was supported by in silico simulations that pentamidine binding rendered most regions of MD2 to be more flexible. Pentamidine was found to inhibit the formation of TLR4/MD2/MyD88 complex and the activation of TLR4 signaling axes of NF-κB and MAPKs, therefore blocking LPS-induced TLR4 signaling downstream pro-inflammatory factors NO, TNF-α, and IL-1β. The bioisosteric replacement of the methylene group at the center 13’ site of pentamidine by the ether oxygen group significantly decreased its interactions with MD2 and abolished its TLR4 antagonist activity. Furthermore, pentamidine enhanced the survival rate of septic mice and exerted an anti-inflammatory effect on organs. All these data provided strong evidence that pentamidine may be an effective drug in alleviating inflammation and sepsis.